Translation and affect essays on sticky affects and translational affective labour - Koskinen, Kaisa (Benjamins translation library, 2020)
"In an age of AI and automated translation, the affective remains a decisively human condition. Translation and Affect is a collection of essays that investigate the role of affects and emotions across the spectrum of translatorial activities and areas, from public service interpreting to multilingual poetry recitals, from translator training to translation technology. In an effort at creating a consilient approach that bridges different research traditions in Translation Studies, Koskinen uses affective labour and affects and their stickiness as a lens to understand how it feels to translate and how translations feel. Written in a personal and engaging style, the book encourages readers interested in translation issues to look at translation as an affective practice and to explore and reflect their own ways of living with translation"--